Subcutaneous fat necrosis after selective head cooling in an infant. Issue 2 (16th April 2013) - Kuboi, Toru; Kusaka, Takashi; Okazaki, Kaoru; Kaku, Uiko; Kakinuma, Ryota; Kondo, Masatoshi; Nishida, Akira
Abstract Hypoxic‐ischemic encephalopathy in neonates causes irreversible damage to tissue and organs and results in multiple organ failure and poor outcome. Therapeutic hypothermia is the most effective therapy in neonates with hypoxic‐ischemic encephalopathy. We report here a case of subcutaneous fat necrosis (SCFN) after therapeutic hypothermia by selective head cooling. Selective head cooling was provided for 72 h after birth. SCFN developed on the patient's cheeks and back at the age of 21 days. Thus, SCFN may be caused by selective head cooling, similarly to whole‐body cooling.